ANALISIS PENDAPATAN DAN PEMASARAN USAHATANI KOPI DI KECAMATAN WAY RATAI KABUPATEN PESAWARAN - Kartika Ruri Setyo Dewi; Wuryaningsih Dwi Sayekti; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analyze income  of arabika and robusta coffee farming,  and the marketing channel patern.  This research was taken in Harapan Jaya and Pesawaran Indah Villages, Way Ratai District, Pesawaran Regency. The sample of this study consisted of 30 robusta farmers and 13 arabica coffee farmers. The farming subsystem was analyzed descriptive quantitatively to analyze the farmer's income in the last year and to assess the feasibility of farming.  The marketing channel pattern was analyzed descriptive qualitatively to determine the pattern of marketing channels of arabica and robusta coffee.  The results showed arabica and robusta coffee farming in Way Ratai District is profitable. Eight percent of arabica coffee farmers used marketing channel II as the most efficient marketing channel, and 40 % of robusta coffee farmers used channel II as the most efficient marketing channel because it has the shortest marketing chain. Keywords: arabica, coffee, channel, income, marketing, robusta.